SMART LIBRARY DESIGN FOR FLOWAUTOMATIONANDEFFICIENCY IMPROVEMENT - Nimita, Fanny; Rosetia, Amanda (Universitas Telkom, 2023)
The library is a public facility that has a very positive impact on the wider community. However, the rapid development of technology and information has resulted in many conventional libraries being abandoned by current library users, namely generation Z. The systems used in conventional libraries can no longer meet the needs of generation Z who want to do things independently by getting fast, easy and efficient results. Thus, the design of a self-service library based on smart architecture is a solution to solve this problem. With the use of Radio Frequency Identification (RFID) technology, Internet of Things (IoT), and Building Automation System (BAS) systems in designing self-service libraries, a library building can be referred to as a smart library. The design of this smart library aims to increase efficiency and flow automation in the library so that it can meet the needs of generation Z and can be used properly by other library visitors. The method used in this study is a descriptive qualitative method by comparing case studies in 3 buildings to analyze the novelty elements that the researcher wants to get. So that this research can provide recommendations on the organization of library building spaces with automation flow to increase efficiency. Keywords : Smart Library, Self-Service, RFID (Radio Frequency Identification), IoT (Internet of Things), BAS (Building Automation System)